2008
DOI: 10.1111/j.1365-2672.2007.03699.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc bacitracin, bird age and access to range on bacterial microbiota in the ileum and caeca of broiler chickens

Abstract: Aims:  Determining the effects of zinc bacitracin, bird age and access to range on bacterial microbiota in the ileum and caeca of broilers. Methods and Results:  16S rRNA gene‐based polymerase chain reaction‐based denaturing gradient gel electrophoresis (PCR–DGGE) profiling, DNA sequencing and real‐time quantitative PCR techniques were used. The richness of both ileal and caecal microbiota increased with chicken age. The microbiota from those birds of the same age demonstrated relatively similar PCR–DGGE profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
85
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 38 publications
24
85
2
3
Order By: Relevance
“…Previous studies used both culture-dependent and -independent methods to show an increase in the diversity of the bacterial community in the ileum and cecum as a bird ages (Knarreborg et al, 2002;van der Wielen et al, 2002;Hume et al, 2003;Gong et al, 2008). Our data agree with these observations.…”
Section: Group C Genussupporting
confidence: 82%
“…Previous studies used both culture-dependent and -independent methods to show an increase in the diversity of the bacterial community in the ileum and cecum as a bird ages (Knarreborg et al, 2002;van der Wielen et al, 2002;Hume et al, 2003;Gong et al, 2008). Our data agree with these observations.…”
Section: Group C Genussupporting
confidence: 82%
“…The lack of differentiation between juvenile and adult community structures is an interesting finding, as strong differences have been reported for other avian systems in which the juveniles were of an age similar to (32,36) or older than (33) the juveniles studied here. Despite the lack of difference in community structure, some OTUs varied significantly in abundance between younger and older birds, likely reflecting at least some role of bird age in shaping the microbiota.…”
Section: Discussionmentioning
confidence: 78%
“…Previous research into the development of the gut microbiota in other host species has shown that the microbiota of juveniles differs significantly from that of adults in both avians and mammals (32)(33)(34)(35)(36), although it is not clear whether this pattern is reflected in the kakapo (12). In many avian species, the juvenile microbiota is a dynamically changing community (37-39) that gradually develops toward the adult community structure (33,36), but the changes in microbiota as the subject ages vary by host.…”
mentioning
confidence: 98%
“…Furthermore, it was observed that the effect on pancreatic enzymate activity was most evident in 7-d of old broilers, as shown by the influence on amylase, trypsin and chymotrypsin activities. This age is crucial for broiler development, as, once the chick hatches, the gastrointestinal tract rapidly develops in relation to their body development and is colonized by microbial populations, which may or may not be beneficial (GONG et al, 2008).…”
Section: Discussionmentioning
confidence: 99%